The Role of Youth Organizations Village in Developing Talents for Slow Learning Students - Fitria Ayu Aryanti; Minsih; Choiriyah Widyasari (Universitas Pendidikan Ganesha, 2023)
Talent is a special potential that exists in every child, including children in the slow learner category. It takes efforts from various parties to develop a talent from slow learner students, one of which is Youth Organizations. The purpose of this study was to analyse the role of the Village Youth Organization in developing students' talents in the slow learner category. The method in this study uses a qualitative approach, with an exploratory descriptive design. The research subjects included slow learner students, teachers, and members of Youth Organizations. Data collection techniques are using observation and interviews. Data analysis techniques include data reduction, data display, and data verification. The results of the study show that the types of talents possessed by slow learners include football, painting, and singing. The role of Youth Organizations in efforts to develop the talents of slow learner children is to facilitate every activity that is needed to develop children's potential such as empowering soccer, volleyball activities, holding painting competitions, and calling to prayer competitions. The conclusion in this study is that most of the talents of slow learner children are in sports, where developing their talents is facilitated by holding several competitions and forming a sports team.